Task aversiveness dan prokrastinasi akademik pada mahasiswa - Rochmah Kurniawati; Herlan Pratikto; Suhadianto (INNER: Journal of Psychological Research, 2022)
Abstract This study aims to determine the relationship between task aversivenest and academic procrastination in students who take online lectures. This study involved 81 students as participants who were selected using incidental sampling technique. The variables in this study were measured using the academic procrastination scale and the task aversiveness scale. The data analysis technique in this study uses Spearma's Rho correlation. Based on the results of data analysis, the correlation coefficient rxy = 0.913 with a significance value of p = 0.000 (p < 0.01). That is, there is a very significant positive relationship between task aversiveness and academic procrastination. The results of this study reveal that there is a very significant positive relationship between task aversiveness and academic procrastination. The effective contribution of the task aversivenest variable to the academic procrastination variable is 87.6%. Keywords: Task Aversiveness, Academic Procrastination.